The problems of Ukrainian studies of fairy tales in the paradigm of research - Карпенко, Світлана Дмитрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Studying the folk epic genres of the epic fantasy for two centuries was a discursive expression of the positions of representatives of different folkloric schools. Starting in the 19th century with commentary collections, the fairy tale genre has gained tremendous scope for study in synchrony and diachrony, affecting a wide range of tangible sciences: philosophy, history, sociology, archeology, anthropology, biology, geography, cultural studies, psychology, linguistics and dialectology. Encouraged by the rich folk-poetic heritage and scientific research of the preceding scientists of the nineteenth century and folklorists of the twentieth century prepared the ground for a deep exploration of the fairy tales. It has become a cultural phenomenon, the object of studies and researches in various fields of knowledge (mostly humanitarian), natural sciences and exact (mathematical) sciences. The nature of the fairy tale, in its very basics, is philosophical: it is wise, effective (fairytale therapy), explains many phenomena of being in a society. According to comparativists, a fairy tale is a philosophy of a certain ethnos in verbal and non-verbal (semiotic, text) form.The article is deals with evaluation of the discourses in the Ukrainian fairylore concerning various aspects of the studying of folk tales: putting texts on paper, studying different folkloristic schools, the relationship of the storyteller’s personality with his social role, etc. Attention is drawn to the dynamics of fairylore as a separate branch of science, with a sufficiently well-developed apparatus for studying folk epics. The theoretical concepts are illustrated with practical references to sources, native and foreign scientists, and scientific centers that are authoritative in various professional discourses on the study of fairytale narrative. Conclusions have been made about the need for further comprehensive study of folk tales, production of generalizing works on Ukrainian fairylore, separate analytical monographs on history, theory and practice of this subject. The analyzed discourses around the folk tale have become a positive factor in the dynamics of Ukrainian fairytale in general.